A matter of scale: how emerging technologies are redefining our view of chromosome architecture. Issue 8 (August 2015) - Cattoni, Diego I.; Valeri, Alessandro; Le Gall, Antoine; Nollmann, Marcelo
Highlights Genomewide technologies reveal the 3D folding of chromosomes at kbp resolution. Recent use of single molecule and super-resolution microscopies has begun to uncover principles of chromatin organization with unprecedented spatial and temporal resolution. DNA is packaged into discrete, physically isolated chromosomal modules often associated with specific epigenetic markers.